Pengaruh Beban Gaji terhadap Laba Bersih PT. Astra International Tbk (Jurnal Ekonomi Bisnis dan Akuntansi, 2024)
This study aims to examine the extent to which salary costs affect net profit at PT Astra International Tbk. This topic was chosen because salary costs are a key component in a company's cost structure that can significantly impact profitability. Through regression analysis of the company's historical financial data, this study processes information using Microsoft Excel to obtain an accurate quantitative picture of the relationship between salary expenses and net profit. The data analyzed includes annual financial statements for a specific period that represent the company's real conditions. The research method uses a quantitative approach with a focus on testing the relationship between the independent variable (salary costs) and the dependent variable (net profit). The analysis process includes data processing, significance testing, and interpretation of regression coefficient values. The results of the analysis indicate a significant relationship between salary expenses and the company's net profit, with a P-value of 0.0000. This value indicates that the effect of salary costs on net profit is statistically very strong and does not occur by chance. This finding reflects that although salary costs are a significant expense, the company has positive expectations regarding their contribution to supporting productivity and achieving financial targets. Effectively managed salary costs can be an investment for the company in retaining and improving employee performance, which in turn has an impact on increasing net profit. The practical implication of this research is the need for PT Astra International Tbk's management to optimize payroll cost management by considering both efficiency and effectiveness. An appropriate strategy for managing payroll costs not only supports profitability but also aligns with the company's social responsibility for employee welfare. This way, the company can achieve a balance between financial goals and long-term sustainability.